ANALYZING PERCEPTIONS OF SOCIAL STUDIES TEACHERS ON PROJECT STUDIES IN THE 6th AND 7th GRADE SOCIAL STUDIES LESSONS OF PRIMARY SCHOOLS - İBRET, B. Ünal; RECEPOĞLU, Ergün; KARASU, Emine (The İnternational Journal of Social Sciences vol 6 no 1, 2012)
The aim of this study is to evaluate social studies teachers' perceptions on project studies in primary schools in terms of some variables (gender, graduated faculty, years in profession, and participation to in-service training). For this purpose, a questionnaire is prepared in order to elicit opinions of 25 social studies teachers from 22 primary schools of Ministry of National Education in the province of Kastamonu about their project studies on social studies lessons. Reliability coefficient of the questionnaire was 0.90. As a result of the survey conducted with teachers of social studies teachers, opinions of the teachers about the project studies being implemented in social studies classes do not show a statistically significant difference in terms of gender, years in profession, and participation to in-service training that they have received, but it was observed that the teachers who graduated from faculty of education have more positive views on the project studies than other social studies teachers.
Keywords: Social studies, social studies teacher, project, teachers' perceptions